Neuroeconomics: a review based on scientific mapping techniques (2021)
Neuroeconomics is a multidisciplinary field, which articulates the knowledge of areas such as economics, psychology and neuroscience, and which studies brain behavior in decision-making. Through a literature review, the evolution of research in neuroeconomics is presented. For this, scientific mapping techniques are used, supported by bibliometric tools. The search was carried out in the WoS and Scopus databases, and the information obtained was processed with the Bibliometrix and Gephi tools. The documents were classified according to their relevance, into three categories: classic, structural and current. Then, through an analysis of co-citations and clustering, five lines or currents of research in the area were identified and analyzed, namely: economic choices, social choice, considerations on neuroeconomics, consumer neuroscience and behavior and brain stimulation . It concludes with the need to find and standardize a research methodology, in which the criteria converge to strengthen the results of the research carried out, since the limitations of current methodologies cannot be ignored.